2021
DOI: 10.1136/bcr-2021-244501
|View full text |Cite
|
Sign up to set email alerts
|

Abdominotransanal resection of a strangulated rectal carcinosarcoma

Abstract: This is a case of a 75-year-old man who presented with a 7-month history of a reducible rectal mass. The patient came to the emergency department with a prolapsed necrotic bowel involving a strangulated segment with the rectal mass. He underwent an abdominotransanal resection through a combined abdominal and perineal approach. His postoperative course was unremarkable. Histopathological and immunohistochemical studies showed a rectal carcinosarcoma. Because of a state-mandated lockdown due to the COVID-19 pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In our review, males gender predominated development of SARS-CoV-2 illness in CRC patients, a finding suggested in most of the reports [ 9 , 11 , 14 , 16 , 17 , 25 , 27 , 28 , 30 , 32 – 35 , 47 , 52 59 , 61 , 62 , 71 , 72 , 74 , 75 , 77 , 81 85 ] and in contradiction with data from other reports suggesting an equal proportion of COVID-19 cases in CRC patients for both genders [ 14 , 23 , 29 , 31 , 60 , 80 ] or patients with CRC and SARS-CoV-2 illness were mostly females [ 11 , 36 , 46 , 49 , 50 , 66 , 67 , 76 ]. This review reflects previous studies in showing that the overall incidence of CRC is higher in males than in females [ 99 101 ].…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…In our review, males gender predominated development of SARS-CoV-2 illness in CRC patients, a finding suggested in most of the reports [ 9 , 11 , 14 , 16 , 17 , 25 , 27 , 28 , 30 , 32 – 35 , 47 , 52 59 , 61 , 62 , 71 , 72 , 74 , 75 , 77 , 81 85 ] and in contradiction with data from other reports suggesting an equal proportion of COVID-19 cases in CRC patients for both genders [ 14 , 23 , 29 , 31 , 60 , 80 ] or patients with CRC and SARS-CoV-2 illness were mostly females [ 11 , 36 , 46 , 49 , 50 , 66 , 67 , 76 ]. This review reflects previous studies in showing that the overall incidence of CRC is higher in males than in females [ 99 101 ].…”
Section: Discussionsupporting
confidence: 57%
“…The detailed characteristics of the included studies are shown in Table 1 . There were 16 case report [ 16 , 32 , 46 , 48 – 50 , 52 , 54 , 55 , 59 , 66 , 67 , 71 , 75 , 82 , 84 ], 9 case series, 41 cohort [ 8 17 , 23 , 25 , 26 , 29 , 31 , 34 , 43 45 , 51 , 53 , 56 58 , 60 – 65 , 68 70 , 73 , 74 , 77 , 79 , 80 , 83 , 85 ], 2 cross-sectional [ 72 , 76 ] and 1 case–control [ 81 ] studies. These studies were conducted in China ( n = 15), Italy ( n = 8), United States ( n = 6), United Kingdom ( n = 6), Spain ( n = 5), India ( n = 4), France ( n = 3), Turkey ( n = 2), Brazil ( n = 2), Japan ( n = 2), Colombia ( n = 1), Philippines ( n = 1), Poland ( n = 1), Iran ( n = 1), The Netherlands ( n = 1), Belgium ( n = 1), United Arab Emirates ( n = 1), Mexico ( n = 1), Sweden ( n = 1), Austria ( n = 1), Hungary ( n = 1), Australia ( n = 1), and Chile ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations